"Nwuna׳s body is so sexy": Pop culture and the chronotopic formulations of kinship terms in Korean. (March 2017) - Brown, Lucien
Abstract: This paper examines the indexical and chronotopic meanings of two Korean kinship terms, oppa 'older brother of woman' and nwuna 'older sister of a man', as they emerge in South Korean popular culture. These kinship terms are commonly used in South Korean society not just to address siblings, but in a tropical sense to address intimates of superior age to the speaker, extending to romantic contexts. The paper demonstrates that oppa and nwuna become chronotopic spaces for negotiation between traditional Korean morals and gender roles tied up in the status and intimacy indexed by these forms, and new competing discourses of gender equality, free love, consumerism and enlightenment. Crucially, the analysis shows that the underlying kinship metaphors contained in oppa and nwuna play a crucial role in negotiating the balance between modernity and tradition, particularly in the depiction of sex and romance in Korean popular culture. By packaging romance and sex within the idiom of kinship, sexual desires and fantasies are rendered innocent and pure, or obscured altogether, thus allowing Korean popular culture to escape censure for being overtly sexually provocative.